1991
DOI: 10.1111/j.1471-0528.1991.tb15403.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of urinary symptoms in early pregnancy

Abstract: Objectives-To determine the correlation between lower urinary tract symptoms and urodynamic findings in early pregnancy. Setting-The termination clinic and gynaecology ward at King's College Hospital. Design-Observational study. Subjects47 women before termination of pregnancy at between 6 and 15 weeks. Interventions-Women filled in symptom questionnaires and then had urodynamic investigations, consisting of uroflowmetry and subtracted provoked cystometry. Main outcome measures-The occurrence of lower urinary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
35
1
2

Year Published

2001
2001
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 7 publications
4
35
1
2
Order By: Relevance
“…Urge incontinence during pregnancy has been reported in 12% of the primiparae and 19% of the multiparae [Stanton et al, 1980], similar to ¢ndings by Cutner et al [1991]. In a small sample of 28 women in late pregnancy, Cutner et al [1992] reported 43% with history of urge incontinence, but the urodynamic testing showed poor correlation with detrusor instability [Cutner et al, 1992].…”
Section: Luts During Pregnancy Prevalencesupporting
confidence: 63%
“…Urge incontinence during pregnancy has been reported in 12% of the primiparae and 19% of the multiparae [Stanton et al, 1980], similar to ¢ndings by Cutner et al [1991]. In a small sample of 28 women in late pregnancy, Cutner et al [1992] reported 43% with history of urge incontinence, but the urodynamic testing showed poor correlation with detrusor instability [Cutner et al, 1992].…”
Section: Luts During Pregnancy Prevalencesupporting
confidence: 63%
“…Stanton et al [12] reported similar results. In a study conducted at first trimester, rates of frequency, nocturia, incomplete emptying and weak stream were detected as 40, 23, 32 and 30%, respectively [13]. Our results are in agreement with the reports of Cutner et al [11] and Stanton et al [12], especially in frequency.…”
Section: Discussionsupporting
confidence: 83%
“…The reported range of incidence rates for antepartum and postpartum urinary incontinence are approximately 24 -61 and 6-38%, respectively [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]. These broad ranges are likely due to differences in the definition and detection method of urinary incontinence and the subject's parity [22].…”
Section: Introductionmentioning
confidence: 99%